Internal corrosion of connections, valves in domestic drinking water distribution systems - Dionicio Padilla, Eusebio (2000)
The research is done to materials that have already failed the corrosion that comes from leading domestic drinking water installations. In this first part of a zinc alloy, Zamak is studied, used as a stopper in a galvanized "T". The material has worked as a sacrificial anode to protect the steel for 4 years. Exfoliating how corrosion occurs in the material.